The macroeconomic effects of trade tariffs: Revisiting the Lerner symmetry result - Jesper Lindé; Andrea Pescatori (Sveriges Riksbank, 2019)
We study the robustness of the Lerner symmetry result in an open economy New Keynesian model with price rigidities. While the Lerner symmetry result, i.e. the absence of allocative and trade-flow effects of an equally-sized change in import tariff and export subsidy, holds up approximately for a number of alternative assumptions, we obtain quantitatively important long-term deviations under complete international asset markets. Direct pass-through of tariffs and subsidies to prices and slow exchange rate adjustment can also generate signi.cant short-term deviations from Lerner. Deviations from symmetry, however, do not necessarily imply an impact on global output and are often limited to a redistribution of production and consumption across countries. Finally, we quantify the macroeconomic costs of a trade war and find that they can be substantial, with permanently lower income and trade volumes. However, a fully symmetric retaliation to an unilaterally imposed border adjustment tax can prevent any sizable adverse real or nominal effects.
Keywords: E52; E58; 330; Import Tariffs; Export Subsidies; Lerner Condition; Incomplete Markets; Complete Markets; Border Adjustment Tax; Trade War; New Keynesian open-economy model; Importbeschränkung; Exportsubvention; Handelseffekt; Konjunktur; Handelskonflikt; Soziale Kosten; Offene Volkswirtschaft; Neoklassische Synthese; Theorie